Populations of the Beet Cyst Nematode Heterodera schachtii Exhibit Strong Differences in Their Life-History Traits Across Changing Thermal Conditions - Fournet, Sylvain; Pellan, Lucile; Porte, Catherine; Piriou, Christophe; Grenier, Eric; Montarry, Josselin (Frontiers in Microbiology, 2018)
It is widely accepted that climate has an essential influence on the distribution of species and that temperature is the major abiotic factor that affects their life-history traits. Species with very restricted active dispersal abilities and a wide geographical distribution are thus expected to encompass distinct populations adapted to contrasted local conditions. The beet cyst nematode Heterodera schachtii is a good biological model to study temperature adaptation in populations collected from different environments. Here, we tested the hypothesis of local adaptation to temperature using seven field populations of H. schachtii from Morocco, Spain, France, Germany, Austria, Poland and Ukraine. We tested hatching and multiplication rates of each population at different temperatures, as well as hatching rates of each population after storage at different temperatures - simulating survival conditions during the inter-cropping period. Results showed a strong temperature effect on the life-history traits explored. Temperature impact on hatching (at different temperatures and after storage at different temperatures) depended on the origin of populations, separating southern from northern ones. Surprisingly, low temperatures influenced hatching less in southern populations. However, for these populations, a storage period at low temperatures strongly reduce subsequent hatching. Conversely, nematode multiplication was not differentially affected by temperatures, as favorable conditions for the host are also favorable for the parasite. Moreover, the relationships between the level of population specialization and population genetic diversity was explored and allow to discuss more in depth our results.